Convergent Evolution of Armor: Thermal Resistance in Deep-Sea Hydrothermal Vent Crustaceans - Boongho Cho; Sook-Jin Jang; Hee-seung Hwang; Taewon Kim (Biology)
Organisms occupy diverse ecological niches worldwide, each with characteristics finely evolved for their environments. Crustaceans residing in deep-sea hydrothermal vents, recognized as one of Earth’s extreme environments, may have adapted to withstand severe conditions, including elevated temperatures and pressure. This study compares the exoskeletons of two vent crustaceans (bythograeid crab Austinograea sp. and squat lobster Munidopsis lauensis) with four coastal species (Asian paddle crabs, blue crab, hermit crab, and mantis shrimp) to identify traits influenced by vent environments. The goal was to identify distinctive exoskeletal characteristics commonly observed in vent crustaceans, resulting from their exposure to severe abiotic factors, including elevated temperatures and pressures, found in vent environments. Results show that the exoskeletons of vent crustaceans demonstrated significantly enhanced thermal stability compared to coastal species. These vent crustaceans consistently featured exoskeletons characterized by a reduced proportion of volatile components, such as water, and an increased proportion of CaCO3, compared with coastal crustaceans. Furthermore, vent crustaceans lacked carotenoid pigments that had low heat resistance. However, no apparent differences were observed in the mechanical properties. Our findings suggest that the similar composition of exoskeletons in vent crustaceans evolved convergently to withstand high temperatures.